Does Haloperidol Prophylaxis Reduce Ketamine-Induced Emergence Delirium in Children? - Amr, Mostafa A. M. (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2013)
OBJECTIVES: Ketamine is a non-barbiturate agent with rapid action onset that induces profound sedation; however, some emergency physicians tend not to use ketamine because of the risk of emergence delirium (ED). This study aimed to evaluate the effectiveness of haloperidol prophylaxis in postoperative ketamine delirium in children. METHODS: Prospective data relating to any emergence dreams, delirium, hallucinations, agitation, crying, altered perceptions, and necessary interventions were recorded in consecutive cases of ketamine delirium in patients attending Mansoura University Hospital, Egypt, from June 2010 to May 2011. RESULTS: A total of 537 records were available for analysis. Of those, 267 received prophylactic haloperidol (49.7%). There were significant differences between the two groups regarding post-anaesthetic care unit behaviour. The ketamine-haloperidol groups included more patients who were sleepy, calm (P ≤0.01) and less irritable (P ≤0.01), with a lower incidence of crying (P ≤0.01) and disorientation (P ≤0.01). CONCLUSION: We found that preoperative administration of haloperidol decreases the incidence of postoperative delirium in a sample of Egyptian children undergoing minor surgery. This is congruent with earlier work conducted in adults. This work carries great hope to decrease and even prevent ED in hospitalised, non-surgical patients.